Cephalosporins: A Focus on Side Chains and β-Lactam Cross-Reactivity - Saira B. Chaudhry; Michael P. Veve; Jamie L. Wagner (MDPI AG, 2019)
Cephalosporins are among the most commonly prescribed antibiotic classes due to their wide clinical utility and general tolerability, with approximately 1−3% of the population reporting a cephalosporin allergy. However, clinicians may avoid the use of cephalosporins in patients with reported penicillin allergies despite the low potential for cross-reactivity. The misdiagnosis of β-lactam allergies and misunderstanding of cross-reactivity among β-lactams, including within the cephalosporin class, often leads to use of broader spectrum antibiotics with poor safety and efficacy profiles and represents a serious obstacle for antimicrobial stewardship. Risk factors for cephalosporin allergies are broad and include female sex, advanced age, and a history of another antibiotic or penicillin allergy; however, cephalosporins are readily tolerated even among individuals with true immediate-type allergies to penicillins. Cephalosporin cross-reactivity potential is related to the structural R1 side chain, and clinicians should be cognizant of R1 side chain similarities when prescribing alternate β-lactams in allergic individuals or when new cephalosporins are brought to market. Clinicians should consider the low likelihood of true cephalosporin allergy when clinically indicated. The purpose of this review is to provide an overview of the role of cephalosporins in clinical practice, and to highlight the incidence of, risk factors for, and cross-reactivity of cephalosporins with other antibiotics.